Factors affecting receptiveness of non-Muslim country's halal food products by urban Malay Muslims / Hasman Abdul Manan - Abdul Manan, Hasman (2018)
The study offered one of the early initiatives in exploring urban Malay Muslim consumers' food-related behaviors toward Halal food products from non-Muslim countries; within a collectivist and urban social setting. The conceptual framework was adopted from the Theory of Planned Behavior and later extended to include three new variables based on empirical evidence in existing literature from several fields of studies. Structural equation modeling and Statistical Package for the Social Sciences were the statistical procedures for a sample of 450 urban Malay Muslims. The results demonstrated the proposed structural model appropriately fits the observed data hence, the results allowed the study to draw its conclusions. Perceived knowledge had successfully predicted trust, subjective norm, and perceived behavioral control; however, it did not show any relationships with attitude and receptiveness.